An Analysis of Responses to Sexual Assault against Women in Public Space: Practical Gender Needs or Strategic Gender Interests? - María Silvestre Cabrera; Iratxe Aristegui Fradua; Raquel Royo Prieto (Social Sciences, 2023)
This article focuses on sexual violence and the learned fear of rape experienced by women in their use of public space, understood as social constructions of a system of domination. We analyze a series of data, drawn from secondary sources, on the prevalence and perception of sexual assault in public space. This data confirms that sexual assault in public spaces is a real risk and that, as such, it is perceived and experienced by the majority of women. We have also selected and presented a series of institutional initiatives aimed at preventing sexual assaults on women in public spaces at night-time. Finally, we have constructed an index to study whether the selected institutional responses respond to practical gender needs or to strategic gender interests. The article concludes that all of these initiatives have a greater impact in the area of gender needs, but they are not able to reverse the structural causes of sexual assault or to contribute to true social change.